Fracture-based interface model for NSM FRP systems in concrete - Coelho, Mário; Caggiano, Antonio; Sena-Cruz, José; Neves, Luís C. (Elsevier, 2016)
This paper introduces a numerical simulation tool using the Finite Element Method (FEM) for near-surface mounted (NSM) strengthening technique using fibre reinforced polymers (FRP) applied to concrete elements.